Knowledge management system in a higher education institution: Development of an expertise search system. Issue 4 (June 2021) - Sugianto,; Abidin, Z; Putra, A T; Budiman, K
Abstract: Knowledge management constitutes determining factors for organisational effectiveness, organisational performance, and sustainable competitive advantage in higher education institutions (HEIs). HEIs create new knowledge through research works and community services, distribute knowledge through teaching and learning, and transfer knowledge through consultancies and scientific discussions. A knowledge management system (KMS) is considered essential for HEIs to facilitate knowledge management. This paper outlines the KMS development process of the Faculty of Mathematics and Natural Sciences of Universitas Negeri Semarang as a platform for advancing the faculty as an organisation. Data collections were conducted through forum discussions to gather information and identify current issues related to data used in KMS development. Some information technology experts, faculties, and top management staff were actively involved in the discussions. The obtained data were analysed and then applied in the system, namely the expertise database and conference database. The iterative model was employed as a guideline for the development of KMS. This model enables the developer to revisit the system once it needs to be updated in the future.